Refocusing and Reshaping of Highly Pathogenic Avian Influenza Preventive Strategies in Rural Settings - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2007)
Highly Pathogenic Avian Influenza Type A H5N1 subtype is a viral zoonotic disease that has infected and killed birds and humans in SE Asia, Africa and Europe since late 2003. Incendiary media reports, mob hype, dire forecasts and misinformation have unintentionally portrayed this animal and human health issue as an inevitable global disaster. Infected and at-risk countries can implement preventive and corrective disease mitigation measures. This disease can be successfully managed at its source by channelling efforts into two areas: communication and education. If contact conditions between virus and healthy birds can be prevented or minimized; most other emergency corrective measures become provisional. Extensive public awareness about prevention needs to be raised, particularly amongst veterinary services and bird owners, keepers and caregivers.